Felicidad : inteligencia emocional - Gilbert, Daniel (BookaVivo, 2022)
What is the nature of human happiness? How can we achieve it in the professional field? Is it worth pursuing? This book explores the answers to these questions through research that tries to find out, among other things, how happiness can be measured, what are the scenarios where personal behaviors are developed and what are the management techniques that facilitate happiness in people. work place. But it also warns of those aspects of Happiness that advertising has exaggerated.